IMPLEMENTASI KURIKULUM ISMUBA DI SD MUHAMMADIYAH KARANGKAJEN YOGYAKARTA - Wasito Wasito (Universitas Muhammadiyah Prof Dr Hamka, 2019)
The purpose of this study was to describe the implementation ofthe ISMUBA curriculum at Muhammadiyah Elementary SchoolKarangkajen Yogyakarta. This study uses qualitative research.The location of this research at Muhammadiyah ElementarySchool of Karangkajen Yogyakarta. The data were collectedthrough observation, interviews, and documentation. Dataanalysis conducted by researchers is to use inductive methods,namely the process of analyzing based on existing data orobtained later developed with certain patterns with the stages ofreducing data, presenting data, and drawing conclusions. Theresults of the study shows that the implementation of the ISMUBACurriculum at Muhammadiyah Elementary School inKarangkajen Yogyakarta as a whole meet the curriculumimplementation standards. The disadvantage is consistency andcontinuity in implementation, then human Resources is not evenlydistributed in quality. Another thing is that the habitual characterbecomes very strong like getting used to prayer in congregationand alms.